The Role of Community Figures in Fostering Attitudes of Social Concern in the Grogol Youth Association (IRAG) Magelung Village, South Kaliwungu District, Kendal Regency - Dian Annisa; Supriyono PS; Rosalina Ginting (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this research is to find out more about the role of community leaders in fostering an attitude of social care in the Grogol Youth Association (IRAG) in Magelung Village, South Kaliwungu District, Kendal Regency. This type of research uses qualitative methods with a descriptive approach. The data sources used as sources of information are community leaders and village youth. The focus of this research is the role of community leaders in fostering an attitude of social care in the Grogol Youth Association (IRAG) in Magelung Village, South Kaliwungu District, Kendal Regency. The indicators in this research are the role of community leaders as direction makers in fostering attitudes of social care, as representatives and spokespersons in cultivating attitudes of social care, as mediators and facilitators in cultivating attitudes of social care and as integrators in cultivating attitudes of social care. Data collection techniques through observation, interviews and documentation. Data analysis techniques through data collection, data reduction, presentation and drawing conclusions. The results of research related to the role of community leaders in fostering an attitude of social concern in the Grogol Youth Association (IRAG) Magelung Village, South Kaliwungu District, Kendal Regency show that 1) the policy of community leaders in cultivating an attitude of social care for teenagers is to involve teenagers in social activities such as mutual cooperation. . 2) accept the aspirations of residents by providing good responses and scrutinizing them to find solutions. 3) hold joint deliberations to hear or accommodate the problems and difficulties faced so that good solutions can be provided. 4) holding meetings between teenagers and parents with joint deliberations providing ongoing education and examples such as teenagers mingling with other people. The conclusion of this research is that the role of community leaders has been implemented to the maximum extent possible but there are still shortcomings in dealing with teenagers, so community leaders continue to provide direction so that social care attitudes can be implemented.